Environmental and Procedural Justice in a Housing Development Conflict: A Conflict-Transformation Analysis in Medan - Abdul Rahman Siregar; Novi Safriani; Saruhum Rambe; Isra Hasanah (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Urban development is frequently accompanied by conflict between local communities and developers. This study analyzes the dispute between residents of Gedung Johor Subdistrict and the developer of the Oasis Delipolitan housing project in Medan, Indonesia, where residents attribute worsened flooding, traffic congestion, and structural cracks to the project, while the developer contends these problems predated it. The purpose is to diagnose the conflict, map its dynamics, and propose transformation strategies. Employing a mixed-methods design—a survey of 100 residents in three affected neighborhoods, semi-structured interviews with the developer, community leaders, and officials, and field observation—the study applies the Conflict Transformation frameworks of Galtung and Lederach, including the conflict triangle (contradiction–attitude–behaviour) and the transformation of relationships, structures, and discourse. Findings show that material impacts (flooding, congestion, damage) triggered relational impacts (eroded trust, polarization) and procedural impacts (inconsistent grievance handling and perceived tokenistic participation), which residents frame as a breach of environmental justice because they bear the risks while benefits accrue elsewhere. The study proposes a transformation matrix combining substantive technical fixes, relational repair, structural reform of participation, and discursive reframing, arguing that repairing relationships, governance, and narratives can turn development disputes into opportunities for community cohesion and sustainable justice.